A Survey on Approaches for Automatic Fault Detection in Software - Andrey Aleksandrovich Usenok (Безопасность информационных технологий, 2013)
The article is about the detection of failures in software. Several techniques of automatic fault detection reviewed: software probes, concurrent runtime monitoring, dynamic instrumentation and software supervision. A brief analysis of advantages and disadvantages of each method presented at the end of the article.